A Governance Dividend for Sub-Saharan Africa? - Hammadi, Amine (IMF Working Papers; Working Paper, 2019)
Countries in Sub-Saharan Africa (SSA) tend to lag those in most other regions in terms of governance and perceptions of corruption. Weak governance undermines economic performance through various channels, including deficiencies in government functions and distortions to economic incentives. It thus stands to reason that SSA countries could strengthen their economic performance by improving governance and reducing corruption. This paper estimates that strengthening governance and mitigating corruption in the region could be associated with large growth dividends in the long run. While the process would take considerable time and effort, moving the average SSA country governance level to the global average could increase the region's GDP per capita growth by about 1-2 percentage points.